Experimental and computational evidence for C=O π-bonding in [CH2OH]+ and related oxonium ions. Issue 3 (June 2020) - Bowen, Richard D; Martin, William HC; Hudson, Charles E; McAdoo, David J
The question of whether [CH2 OH] + should be described as the hydroxymethyl cation, + CH2 OH, or protonated formaldehyde, CH2 =OH +, is reconsidered in the light of experimental information and new computational evidence. Previous arguments that the charge distribution in [CH2 OH] + may be probed by considering the incremental stabilisation of [CH2 OH] + induced by homologation on carbon (to give [CH3 CHOH] + ) or oxygen (to produce [CH2 OCH3 ] + ) are critically examined. Cation stabilisation energies are shown to be better indicators of the nature of these oxonium ions. Further insight into the structure of larger Cn H2n+1 O + oxonium ions is obtained by considering the site of protonation of enol ethers and related species. Computational information, including AIM (Atoms and Molecules) and NBA (Natural Bond Analysis) charges on the carbon and oxygen atoms in [CH2 OH] + and related species, is considered critically. Particular attention is focused on the calculated bond lengths and barriers to rotation about the C–O bond(s) in [CH2 OH] +, [CH3 CHOH] +, [(CH3 )2 COH] +, CH3 OH and [CH2 OCH3 ] + and the C–N bond in [CH2 NH2 ] + . Trends in these data are consistent with appreciable π-bonding only in the C–O connections which correspond to the C=O bond in the parent aldehyde or ketone from which the oxonium ion may be considered to be derived by protonation or alkyl cationation.